Supporting collaborative business processes: a BPaaS approach. (2018) - Xu, Lai; Vrieze, Paul De
Collaborative business processes are increasingly driven by business flexibility and agility. Cloud-based business process management services have provided small and medium enterprises (SMEs) with a pay-per-use manner for their daily business needs, i.e., some simple business process applications, e.g., salesforce provides cloud-based CRM to boost SMEs' sales. This raises the question how can cloud-based business process management solutions support the fast pace of change of business collaborations among business partners? For example, collaborative processes for managing industrial incidents are short term, low frequency processes. This paper proposes an architecture meta-model, which is used to design the concrete architecture and to further analyse the performance of the proposed solution. A real world case of collaborative processes for incident and maintenance notifications is used to explain the design and implementation of the cloud-based solution for supporting collaborative business processes. Service improvement of the new solution and computing power costs are analysed accordingly.